Project Management of Strengthening the Profie of Pancasila Students in Eementary Schools in Geger District, Madiun Regency - Khusnia Ekawati; Sri Marmoah; Kusdianto Kusdianto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This research describes the implementation of a project to strengthen the profile of Pancasila students (P-5) at SD Geger sub-district. The aim of this research is to describe the implementation of P-5 in elementary schools in Geger sub-district. This type of research is descriptive qualitative. The data source is P-5 activities. Data collection through observation, interviews and documentation, data analysis using the interactive model from Miles and Haberman. The results of the research are the implementation of holistic, contextual, student-centered education, and a new exploration of 12 elementary schools.